Thermophysical features of Ellis hybrid nanofluid flow with surface-catalyzed reaction and irreversibility analysis subjected to porous cylindrical surface - Khan, Muhammad Naveed; Ahammad, N. Ameer; Ahmad, Shafiq; Elkotb, Mohamed Abdelghany; Tag-eldin, Elsayed; Guedri, Kamel; Gepreel, Khaled A.; Yassen, Mansour F. (Frontiers in Physics, 2022)
The existing study exposes the irreversibility scrutiny of Ellis hybrid nanofluid flow ( nanoparticles) with homogeneous and heterogeneous reactions towards the horizontal porous stretching cylinder. The energy transportation aspects are investigated with the influence of joule heating and viscous dissipation. The slip and convective boundary conditions are levied on cylindrical surface. The mathematical flow model is transferred into the system of nonlinear ODEs by the usage of suitable transformation. The highly nonlinear systems of equations are tackled numerically with the assistant of BVP4C MATLAB built-in approach. The graphical outcomes are obtained and discussed by the help of graphs. It is noteworthy to see that by growing estimations of the curvature parameter shows opposite behavior on Ellis fluid velocity and entropy generation, which is that entropy generation profile increasing while diminution the fluid velocity. Thinning boundary layers are resisted by elasticity and magnetic fields impact. Further, as the porosity of the liquid phase grows, as a result momentum boundary layer decreases, which is true by realism.